Social Work Practice in Schools: Issues for Consideration - Thuy, Nguyen Thi Bich (VNU Journal of Science: Education Research; Vol 36 No 3DO - 10.25073/2588-1159/vnuer.4411, 2020)
This paper analyzes the existing problems relating to social work practice in schools. Based on the analysis results, the paper proposes several practical solutions for improving the quality of Social Work Practice training in colleges and universities offering this major in the hope of enhancing social workers’ practice in schools.